Perusahaan Rekaman Lokananta, 1956-1990-An: Perkembangan Produksi dan Kiprahnya dalam Penyebarluasan Seni Pertunjukan Jawa Surakarta - Dhanang Respati Puguh (SASDAYA: Gadjah Mada Journal of Humanities, 2018)
This article examines on the role of Lokananta in disseminating Javanese performing arts of Surakarta during 1956-1990. It is focused on records production either in vinyl or tape cassettes and its distribution. This article composed using historical method and utilize wide range of historical sources, such as archives, newspapers, vinyl and cassette covers, articles, books, and oral history. The results showed that during 1957-1971, Lokananta has produced vinyl records which were classified into National Music, Regional Entertainment, and Regional Theatre Music. In that period, Lokananta production was dominated by recording of National Music and Music-Theatre of Central Java. During 1971-1985 Lokananta produced many music and theatre records of Central Java printed into cassette tape. In 1985-1990’s, Lokananta produced and made reproduction on cassette recordings. Quantitatively, production and reproduction recording number has drastically decreased compared to the previous period. Records vinyl and tape cassettes sale, as well as the distribution via Radio Republik Indonesia and private broadcasts, proved that Lokananta has been instrumental in disseminating Javanese performing arts of Surakarta.